Small molecule inhibitors against enteric bacterial glycosyltransferases - Zhu, Congrui (Kansas State University, 2021)
Enteric bacterial pathogens are the major sources of foodborne diseases. Infection caused by these pathogens leads to gastroenteritis thus of great threat to public health. Pathogenic bacteria evolved to develop various secretion systems to deliver virulence proteins termed ‘effectors’. These virulence factors promote the invasion of pathogens as well as evasion of host innate immune response. Type III secretion system (T3SS) is one of the most complex secretion systems used by Gram-negative bacteria Escherichia coli, Salmonella enterica, and Citrobacter rodentium. T3SS resembles a molecular syringe structure to inject secreted effector proteins directly from the bacterial cell into the host cell. Our goal is to look for anti-bacterial virulence therapies by targeting important T3SS effectors. In our first project, we targeted T3SS effector proteins NleB and SseK (NleB ortholog), which are glycosyltransferases that glycosylate protein substrates on arginine residues. This modification is unusual because it occurs on the guanidinium groups of arginines, which are poor nucleophiles, and is distinct from the activity of the mammalian O-linked N-acetylglucosaminyltransferase (OGT). As the deletion of gene nleB significantly attenuates C. rodentium virulence, we aimed to find small molecular inhibitors which specifically bind to NleB. Therefore, we performed high-throughput screening (HTS) assays to identify NleB/SseK inhibitors. We identified two compounds (100066N and 102644N) that significantly inhibited NleB1, SseK1, and SseK2 glycosylation activities. They were also able to inhibit NleB1 glycosylation of the tumor necrosis factor receptor type 1-associated DEATH domain (TRADD) protein in mammalian cells. After pre-incubation with the two compounds in mouse monocyte/macrophage-like cells (RAW264.7), number of Salmonella enterica strain ATCC 14028 which replicated inside RAW264.7 cells greatly reduced 24 h post infection. Results confirmed that 100066N and 102644N can inhibit NleB/SseK activity both in vitro and in vivo. Both compounds can work directly in mammalian cell culture to counter bacterial virulence. Furthermore, 100066N and 102644N show high potential in new drug development because they have advantages of not interfering with bacterial growth curve when added to the LB culture, no significant toxicity to mammalian cells, and do not cross-react with human OGT. However, we encountered difficulties when trying to apply 100066N and 102644N on mice infection models. The two compounds were not easy to synthesize, and their derivatives did not show significant inhibitory effect on bacterial glycosyltransferases. Therefore, in the second project, we screened more NleB/SseK inhibitors by enlarging our libraries to perform HTS assays. These libraries include Analyticon natural products library, ChemDiv 3D Biodiversity, ChemDiv Peptidomimetics, FDA proved drugs, Selleck Bioactives and MayBridge mini library. We identified YM155 (sepantronium bromide) which can inhibit EHEC NleB1, Salmonella SseK1, SseK2, and Citrobacter NleB activities. Like 100066N and 102644N, YM155 also does not interfere with enteric bacterial growth curve when added to the LB culture, has no significant toxicity to mammalian cells nor cross-react with human OGT. Above all, YM155 has the advantage of being more soluble and amenable to chemical derivatization.
Keywords: Type three secretion system effectors; Glycosyltransferase; Enteric bacteria; Small molecule inhibitors